Barbell Technique Associated With Sinus Lift for Horizontal and Vertical Guided Bone Regeneration—Case Report - Costa, Fernanda Calvo [UNESP]; Paradella, Thaís Cachuté [UNESP]; Raldi, Fernando Vagner [UNESP]; Moraes, Michelle Bianchi-de [UNESP]; Nascimento, Rodrigo Dias [UNESP] (Wiley, 2025)
Background: Dental absences are a worldwide issue, affecting patients both socially and functionally. Implant rehabilitation is the gold standard treatment; however, prior bone reconstructions may be necessary. The Barbell Technique is a guided bone regeneration technique recommended for defects of various morphologies, allowing for vertical and horizontal unidirectional or bidirectional regeneration, that is, both on the buccal and palatal/lingual sides. The objective of this paper is to report a case of bone reconstruction in the posterior maxilla prior to implant rehabilitation, where the Barbell Technique was performed together with a sinus lift. Methods: This study consists of a case report of a 77-year-old male patient with the absence of first and second right bicuspids and a history of implant losses in the area. The initial CT scan showed horizontal and vertical alveolar atrophy, making implant placement impossible. Regeneration was performed using a sinus lift for vertical recovery and the Barbell Technique for horizontal regeneration, using xenogeneic bone covered by a collagen membrane. After 6 months, a new CT scan suggested sufficient bone volume, and two implants were guidedly placed based on digital planning. Results: Comparison of CT scans before and after the grafts showed a horizontal bone gain of 70% and a vertical gain of 33%. Six months after the reconstructive surgery, dental implants were placed, followed by the installation of individual crowns after 45 days. At the 24-month follow-up, no complications related to the implants or prostheses were observed. Conclusion: In this clinical case, for the first time in the literature, the association of the techniques allowed the regeneration of the defect, with the subsequent placement of implants in the ideal position and prosthetic rehabilitation.